RESEARCH ON DELIVERING OUTCOME-BASED LEARNING THROUGH BLENDED LEARNING METHODOLOGICAL TOOLS - Otgonbayar Tseveen; Damchaasuren Khorloo (International Journal of Innovative Technologies in Social Science, 2024)
As societal development progresses, the burgeoning demands and expectations for individualized education are on the rise. This necessitates a nuanced shift in educational policies and methodologies to cater to the evolving needs of learners. In recent years, there has been a discernible shift from teacher-centered learning to learner-centered learning. Consequently, the paramount concern lies in optimizing the efficacy of training methodologies. This study aims to investigate the potential of enhancing students’ learning interest and engagement through the application of blended learning methods. The objective of the research is to systematically compare the outcomes, advantages, and disadvantages, and identify the key areas for further improvement.